ASSESSMENT AND RISK MANAGEMENT OF SOCIO-ECONOMIC PROJECTS - Olesia Iastremska; Olha Korolenko (Three Seas Economic Journal, 2021)
The quality of implementation of social programs and projects is a measure of the effectiveness of social policy. Ideally, a social project can be implemented if absolutely everyone is interested: both the participants and those to whom the project affects in one way or another. All stakeholders are members of the value chain and add value to the program to one degree or another. The general purpose of the research work is to substantiate the mechanisms for reconciling the interests of stakeholders and study effective models of social entrepreneurship. Practice proves that the most rational among the known methods of risk management is the stakeholder approach. The main risks in the perception of the quality of social project implementation are “gaps”: a) in knowledge – project implementers misunderstanding of the customer expectations; b) in standards – the inability to set quality standards that meet customer expectations; c) in the effect of implementation – the inability to ensure the quality of project implementation in relation to established standards; e) in communications – the inconsistency of the transmitted information about the quality of the project to the actual level. All these risks are closely linked. Research shows that the greatest risks in the implementation of social projects occur among the “gaps” in standards. Distinctive features of the management process of social programs and projects, which have to be taken into account during the management standards development, are presented in the work of V.M. Burkov. The basis of the formation of the interests harmonization mechanism is the “Stakeholder Interaction Standard AA1000” (Standard AA1000SES), which sets out the basic methods, tools and standards of stakeholders management. The technology of developing of the social project road map is presented in the work of O.V. Ponomarenko. The works of O.I. Datsko are devoted to the study of the role of stakeholders in the view of the projects development with the aim to increase the territories competitiveness. The process of urban development strategy is researched by A.I. Yermolova. Summarizing the above, it should be noted that one of the defining areas of socialization of economic relations in modern Ukraine is the development of social entrepreneurship. Today’s economic, political and social realities necessitate the development of social entrepreneurship from the level of charity to the level of social enterprises, which will not only become a source of material needs for people unable to compete in the labor market, but also help to solve various pressing social problems. The formation of social enterprises should be ensured by a set of legal, economic and ideological guarantees from the state and society. The evolution of social entrepreneurship should be accompanied by the solution of both global (for example, the formation of public consciousness) and applied (for example, for the sustainable social entrepreneurship development it is required to use effective business models) tasks. The method of CBA involves determining the discount rate for social projects, which can be calculated by the model for the assessment of the social border of intertemporal benefits. The following statistical indicators can be used for calculation: the risk to life level, the growth rate of consumption per capita, the elasticity of the marginal social utility of consumption. The calculation uses the arithmetic mean values of these indicators for as long as possible.